PELATIHAN MENYUSUN ANGGARAN UNTUK DAPAT MENINGKATKAN LABA OPERASIONAL - Irna Triannur Lubis (Nusantara Hasana Journal, 2025)
Effective budgeting is one of the keys to improving operational efficiency and company profits. However, many employees in the retail sector still do not have basic skills in designing a systematic budget. This community service activity aims to improve the understanding and ability of Lotte Mart Medan Center Point employees in preparing an efficient and targeted work budget. The implementation method consists of three stages, namely providing budgeting theory material, unit-based budgeting practice, and discussion and evaluation sessions. The results of the activity showed a significant increase in participant understanding, marked by differences in pre-test and post-test scores and high enthusiasm in the practice session. In addition, participants also began to understand the importance of involving all work units in the budgeting process as an effort to control costs and increase operational profits. This activity was concluded to have succeeded in improving basic financial literacy of employees, and it is recommended to be replicated periodically in other work units.